Synergistic effect of electromigration and Joule heating on system level weak-link failure in 2.5D integrated circuits - Liu, Yingxia; Li, Menglu; Kim, Dong Wook; Gu, Sam; Tu, K. N. (Journal of applied physics, 2015)
In system level electromigration test of 2.5D integrated circuits, a failure mode due to synergistic effect of Joule heating and electromigration has been found. In the test circuit, there are three levels of solder joints, two Si chips (one of them has through-Si-via), and one polymer substrate. In addition, there are two redistribution layers; one between every two levels of solder joints. We found that the redistribution layer between the flip chip solder joints and micro-bumps is the weak-link and failed easily by burn-out in electromigration test. The failure is time-dependent with sudden resistance increase. Preliminary simulation results show that Joule heating has a positive feedback to electromigration in the redistribution layer and caused the thermal run-away failure. Joule heating becomes an important reliability issue in the future scaling of semiconductor devices.